Estudy of the pedagogical variables in teaching tasks of football based on the session part - Gamero-Portillo, M.; García-Ceberino, JM.; Feu, S.; Antúnez, A. (SPORT TK-EuroAmerican Journal of Sport Sciences, 2019)
The objective of this study was to analyze the pedagogical variables of the tasks designed by the pre-service teachers for the teaching of school soccer based on the parts of the session. 307 tasks designed by 6 teachers in training have been codified through the Integral System for the Analysis of the Training Tasks (SIATE). The pedagogical variables classified by this system were analyzed: game situation, goalkeeper presence, game phase, content type I and II, specific content, teaching medium, level of opposition, type of participation and Feedback. A descriptive and inferential analysis was carried out using the Chi-Square test, Cramer's V test and the Corrected Typified Waste. The results show significant differences (p <.05) in the design of the tasks for each part of the session with respect to the pedagogical variables, except in the variable type of content II.